Issues and Problems of Implementing Inclusive Education Policies in Elementary Schools - Yuliawati; Permana, Johar; Lasmawan, I Wayan (Universitas Pendidikan Ganesha, 2023)
Optimizing educational services is a concern for all stakeholders, including education services for children with special needs in elementary schools. However, education services for children with special needs in schools have yet to become a priority. This study aims to determine the issues and problems of implementing inclusive education policies in elementary schools. The type of research used in this research is descriptive qualitative. The subjects involved in this study were school principals, teachers, and 4 children with special needs. The data collection technique used in this study was through interviews, observation, and documentation, with the research instrument being an observation guide. The data obtained was then analyzed using qualitative techniques through three stages: data reduction, presentation, and verification. The results of data analysis show that the problems experienced by schools while implementing inclusive education are that there has not been good coordination between inclusive education policymakers and the school in implementing policies regarding procedures and supporting documents for organizing inclusive schools; there is no Special Assistance Teacher (GPK) so that the handling of ABK tends to be the same as other regular students. There is no individual learning curriculum and program, so it still uses the regular curriculum and learning program. These results then show that the implementation of incubation schools in Indonesia still needs to be by the concepts put forward and implementation guidelines, both in terms of students, teacher qualifications, facilities and infrastructure, and parental and community support.